2004
DOI: 10.1016/s0002-9440(10)63135-5
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of Plasminogen Activator Inhibitor-1 in Cardiomyocytes Contributes to Cardiac Fibrosis after Myocardial Infarction

Abstract: Plasminogen activator inhibitor-1 (PAI-1) plays a critical role in tissue fibrosis by inactivating matrix metalloproteinases, which might effect on the progression of left ventricular dysfunction. However, little has been known about the expression of PAI-1 during cardiac remodeling. We used a mouse model of myocardial infarction (MI) by coronary ligation, in which the progression of left ventricular remodeling was confirmed by echocardiography. Histological examination showed that interstitial and perivascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
89
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(98 citation statements)
references
References 47 publications
7
89
1
1
Order By: Relevance
“…Increased expression of PAI-1 in cardiac myocytes has been shown to contribute to cardiac fibrosis in a mouse model of MI [12]. This is in line with an earlier observation by Heymans et al [10] that mice deficient in u-PA, although protected from cardiac rupture after MI initially, showed impaired healing and revascularization and died of heart failure suggesting that proteolytic activity at a particular stage is required to maintain the proper function of the heart.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…Increased expression of PAI-1 in cardiac myocytes has been shown to contribute to cardiac fibrosis in a mouse model of MI [12]. This is in line with an earlier observation by Heymans et al [10] that mice deficient in u-PA, although protected from cardiac rupture after MI initially, showed impaired healing and revascularization and died of heart failure suggesting that proteolytic activity at a particular stage is required to maintain the proper function of the heart.…”
supporting
confidence: 79%
“…Two proteaseprotease inhibitor systems are involved in extracellular matrix (ECM) remodeling in the heart: the plasminogen activator (PA)/plasmin system has been implicated in turnover of ECM in cardiac tissue [10,11]. Takeshita et al showed that PA inhibitor-1 (PAI-1) produced by cardiac myocytes contributes to cardiac fibrosis after MI in mice and increased amounts of PAI-1 were detected in heart of swine with left ventricular hypertrophy [12,13]. The second system involved in ECM remodeling in the heart is the matrix metalloproteinase (MMP)/tissue inhibitor of metalloproteinase (TIMP) system [14].…”
mentioning
confidence: 99%
“…1D, uptake of viable PAI-1 Ϫ/Ϫ neutrophils was dosedependently inhibited by exposure to PAI-1 and was decreased to basal levels after incubation with 1 g/ml PAI-1. Of note, similar or greater concentrations of PAI-1 are found in serum and tissues of patients with inflammatory conditions, such as acute lung injury (15)(16)(17)(18). These data suggest that binding of PAI-1 to viable PAI-1 Ϫ/Ϫ neutrophils blocks their phagocytosis.…”
Section: Pai-1 Deficiency Is Associated With Enhanced Phagocytosis Ofmentioning
confidence: 77%
“…The primary molecules to which PAI-1 binds are urokinase-type plasminogen activator (uPA), tissue-type plasminogen activator (tPA), fibrin, vitronectin, and members of the low density lipoprotein receptor (LRP) family (13,14). Elevated serum and tissue levels of PAI-1 have been found in a number of inflammatory diseases, including myocardial infarction, sepsis, and acute lung injury, with increased circulating PAI-1 levels being associated with unfavorable outcomes (15)(16)(17)(18). Previous studies suggested that microvascular thrombosis associated with inhibition of fibrinolytic processes by PAI-1 and the role of PAI-1 as a chemotactic factor promoting the migration of lymphocytes and neutrophils into inflammatory sites contributed to its inflammatory effects (19)(20)(21).…”
mentioning
confidence: 99%
“…PAI-1 mRNA expression is induced by various humoral factors such as IL-1a, TNF-a, and TGF-b not only in cardiovascular cells but also in cardiac myocytes [43,46,47]. This acute induction of PAI-1 mRNA expression was thought to locally elevate PAI-activity in the heart [47].…”
Section: Discussionmentioning
confidence: 99%